KINETIC AND THERMODYNAMIC PROPERTIES OF MOGANITE, A NOVEL SILICA POLYMORPH - Gislason S.R.; Heaney P.J.; Oelkers E.H.; Schott J. (My University, 1997)
A growing body of evidence reveals that much of the silica that crystallizes at the Earth's surface is a finely intergrown mixture of quartz and moganite. To better understand the behaviour of both solid and aqueous silica in these systems, the kinetics and thermodynamic properties for endmember moganite have been determined as a function of temperature from 25° to 200°C. Because endmember moganite has yet to be found in nature or synthesized in the laboratory, these properties were determined indirectly by (1) measuring quartz dissolution rates at pH 3.5, (2) measuring the dissolution rates of quartz/moganite mixtures of various proportions at pH 3.5 to deduce the endmember moganite dissolution rate, (3) using the principle of detailed balancing and the assumption that silica polymorphs have equal precipitation rates (Rimstidt and Barnes, 1980) to compute the equilibrium constant for the quartz to moganite transformation reaction, and (4) regressing these data together with corresponding values for quartz to generate endmember moganite thermodynamic properties.Equations describing the temperature dependence of the specific dissolution rate of quartz, k+,Si,qtz (mole/m2/s), and moganite, k+,Si,mog (mole/m2/s) at pH 3.5 and far from equilibrium areln k+,Si,qtz = -0.0463 - 80480RT for quartzln k+,Si,mog = -0.975 - 70502RT for moganite which is consistent with activation energy of 80.5 and 70.5 kJ/mol for quartz and moganite, respectively. The specific dissolution rate of moganite is 7.4 times faster than that of quartz at pH 3.5 and 25°C. The surface area of quartz/moganite mixtures increase exponentially with increasing moganite content. It follows that the apparent dissolution and precipitation rate of quartz/moganite mixtures also increases exponentially with moganite content.The standard state enthalpy and Gibbs free energy of formation for moganite from the elements at 25°C and one bar was calculated to be -900.723 and -851.314 kJ/mole which is 10 and 5 kJ/mol, respectively, more positive than those for quartz. The standard state entropy at these conditions is 58.245 J/mole/K, which is 17 J/mol/K greater than that for quartz. The logarithm of the equilibrium constant for moganite hydrolysis is -3.14 at 25°C and one bar, which corresponds to a solubility of 44 mg/kg silica. In contrast, the logarithm of the equilibrium constant for quartz hydrolysis is -4.00 which corresponds to a solubility of 6 mg/kg silica. The difference in the hydrolysis constants decreases with increasing temperature.The relative rapid dissolution rate of moganite and its thermodynamic instability with respect to quartz is consistent with the observation (Heaney and Post, 1992) that moganite is depleted in weathered chert and chalcedony, and it supports the diagenetic silica sequence proposed by Heaney (1995), who documented a scarcity of moganite in rocks older than 100 m.y. It also follows that the high abundance of moganite in recent arid environments is likely due to the lack of water available to mediate the dissolution of moganite and simultaneous precipitation of quartz.